2005
DOI: 10.1002/cjoc.200590993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Activity of CH3OOH and CH3CH2OOH Study on a Photoelectron Spectroscopy

Abstract: The ionization energies of MHP (CH 3 OOH) and EHP (CH 3 CH 2 OOH) have been determined by HeI photoelectron spectroscopy (PES) measurement and both Gaussian-2 (G2) calculation and Hartree-Fock (HF) method on the basis of Koopmans theorem at 6-311+G* basis set level for the first time. The assignment and characterization of PE spectra of MHP and EHP were also supported by the G2 and HF calculations. The first ionization energies of MHP and EHP are 9.87 and 9.65 eV, respectively. Higher solubility of EHP in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…82 ± 0.03 eV, in good agreement with the 9.87 eV by Yi-Min et al12 The other conformer of CH300H+ is 0.30 eV higher in energy and differs in the dihedral angle of the O-OH hindered rotor. As also suggested by the experiments, we found that CH300H+ can undergo the following simple bond scission reactions: the following section, we discuss the key properties of each channel, while more details and figures are provided in the SI-2 part of the Supporting Information.…”
supporting
confidence: 89%
“…82 ± 0.03 eV, in good agreement with the 9.87 eV by Yi-Min et al12 The other conformer of CH300H+ is 0.30 eV higher in energy and differs in the dihedral angle of the O-OH hindered rotor. As also suggested by the experiments, we found that CH300H+ can undergo the following simple bond scission reactions: the following section, we discuss the key properties of each channel, while more details and figures are provided in the SI-2 part of the Supporting Information.…”
supporting
confidence: 89%
“…Concentrations of these organic peroxides in the atmosphere depend not only on their sources, but also on their chemical conversions, which determine their sinks. To date, a number of studies on the atmospheric chemical reactions of MHP and EHP have been carried out 5–21…”
Section: Introductionmentioning
confidence: 99%